Anti-inflammatory action on kidneys of rats of the preparation of polyunsaturated fatty acids (PUFA) - I. P. Pustovoyt; A. P. Levitsky; V. T. Stepan (Kazimierz Wielki University, 2018)
Background. To determine the renoprotective effect of PUFA. Methods. The preparation of essential PUFA "Liposan-C" was used, which was administered to rats on a fat-free diet in an amount of 1% of the diet weight for 32 days. The activity of elastase, urease, lysozyme, catalase and the content of MDA were determined in the homogenate of the kidneys. According to these indicators, the degree of dysbiosis and intensity of inflammation were calculated. Results. A decrease in the activity of urease, elastase and the degree of dysbiosis in rats treated with Liposan-C was established. Conclusion. The drug PUFA "Liposan-C" has anti-inflammatory, antimicrobial and anti-disbiotic effect on the kidneys.